Yxilon: A client-server based statistical environment - Wolfgang Karl Härdle; Sigbert Klinke; Uwe Ziegenhagen (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
Along with many others, we agree that a modern education in statistics needs to incorporate the practical analysis of real datasets, which are usually more complex than the common examples found in standard textbooks. The software used in the teaching of statistics includes standard spreadsheet environments such as OpenOffice and Excel and dedicated commercial and non-commercial packages such as R, Minitab or SPSS. With the freely available Yxilon environment we add another package and proliferate the statistical programming language XploRe, using a modern client/server based architecture. This architecture has the capabilities of serving statistical results in a variety of flavors for different groups of users. In this paper we describe the general setup of the Yxilon environment and present selected technical details.
Keywords: C88; 330; e-learning; statistical software; Computergestütztes Lernen; Statistische Methodenlehre; Theorie